Predictors of Medical Serious Adverse Events in Hip Fracture Patients Treated With Arthroplasty. (November 2020) - Neilly, David; MacDonald, David R. W.; Sprague, Sheila; Bzovsky, Sofia; Axelrod, Daniel; Poolman, Rudolf W.; Frihagen, Frede; Heels-Ansdell, Diane; Bhandari, Mohit; Schemitsch, Emil H.; Stevenson, Iain M.
Abstract : Aim: Patients with hip fractures are often frail with multiple comorbidities and at risk of medical serious adverse events (SAEs). We investigated the HEALTH trial patient population to ascertain predictors of SAEs. Methods: We performed a multivariable Cox regression analysis. Occurrence of SAEs was included as the dependent variable with 31 potential prognostic factors being included as independent variables. Results: One thousand four hundred forty-one patients were included in this analysis. Three hundred seventy (25.6%) patients suffered from an SAE. The most common events were cardiac (38.4%, n = 105), respiratory (20.8%, n = 77), and neurological (14.1%, n = 77). The majority of SAEs (50.8%, n = 188) occurred in the first 90 days after hip fracture with 35.4% occurring in the first 30 days (n = 131). Body mass index (BMI) between 18.5 and 24.9 compared with BMI between 25 and 29.9 [hazard ratio (HR) 1.32, P = 0.03] and receiving a total hip arthroplasty compared with a bipolar hemiarthroplasty (HR 1.36, P = 0.03) were associated with a higher risk of a medical SAE within 24 months of femoral neck fracture. Age ( P = 0.09), use of femoral cement ( P = 0.59), and use of canal pressurization ( P = 0.37) were not associated with a medical SAE. Conclusion: Total hip arthroplasty is associated with more SAEs in the immediate postoperative period, and care should be taken in selecting patients for this treatment compared with a hemiarthroplasty. A higher BMI may be protective in hip fracture patients while age alone does not predict SAEs and neither does the use of femoral cement and/or pressurization. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.